A Prospective Study of Strut versus Miniplate for Fractures of Mandibular Angle. Issue 3 (September 2013) - Xue, Amy S.; Koshy, John C.; Wolfswinkel, Erik M.; Weathers, William M.; Marsack, Kristina P.; Hollier, Larry H.
This prospective randomized clinical trial compared the treatment outcomes of strut plate and Champy miniplate in fixation of mandibular angle fractures. Patients with mandibular angle fracture were consented and enrolled into this study. Exclusion criteria include patients with severely comminuted fractures. The patients were randomly assigned to receive the strut plate or Champy miniplate for angle fracture fixation. Patient demographics, fracture characteristics, operative and postoperative outcomes were collected prospectively. Statistical analysis was performed to evaluate the significance of the outcome. A total of 18 patients were included in this study and randomly assigned to receive either the strut plate or Champy miniplate. Out of which five patients were excluded postoperatively due to complex fracture resulting in postoperative maxillomandibular fixation. The final enrollment was 13 patients, N = 6 (strut) and N = 7 (Champy). There was no statistically significant difference in the pretreatment variables. Nine of these patients had other associated facial fractures, including parasymphyseal and subcondylar fractures. Most of the (11) patients had sufficient follow-up after surgery. Both groups exhibited successful clinical unions of the mandibular angle fractures. The complications associated with the mandibular angle were 20% in the strut plate group and 16.7% in the Champy group. One patient in the strut plate group had a parasymphyseal infection, requiring hardware removal. The strut plate demonstrated comparable surgical outcome as the Champy miniplate. It is a safe and effective alternative for management of mandibular angle fracture.